L-Dopa Feeding Induces Body Growth and Reproductive Conditions in Japanese Quail, Coturnix coturnix Japonica - Prasad, S.K.; Qureshi, Taj N.; Saxena, S.; Qureshi, S.; Mehar, M.; Thakur, S.K. (International Journal of Poultry Science, 2007)
It is obvious from several studies that the different neurotransmitters are associated with various metabolic activities of the body directly or indirectly via their effects on hypothalamic/pituitary hormone but regarding the control of reproductive system catecholamines seem to have a central role. In view of above fact the present study was designed to test whether neurotransmitter precursor L-Dihydroxyphenylalanine (i.e. L-DOPA, a dopamine precursor) feeding, can influence body growth and reproductive conditions in high food value poultry bird Japanese quail, Coturnix coturnix japonica. Experiments were performed in both male and female Japanese quail. Sexually immature (one week old) quail chicks were divided into two groups of 24 birds each. Group-I provided with normal diet and served as control while Group-II (experimental group) provided with food mixed with L-DOPA (50 mg/15 gm food). At the age of 3 weeks (when birds were sexually distinguished) Group-I was divided into two sub groups IA (male) and IIA (female) of six birds each. Similarly Group II was sub divided into IB (male) and IIB (female) of 6 birds each. Observations were made up to the age of 5 weeks. Male experimental group (IB) showed significantly increased testicular activity, cloacal gland volume, body weight, plasma testosterone and LH level in comparison to control (IA). Similarly female experimental group (IIB) showed significantly high weight of reproductive organs (uterus, ovary, oviduct, ovarian follicle), body weight, egg weight and size and number of follicles. On the other hand plasma prolactin level was significantly low in comparison to control (IIA). Results suggest that the development and reproduction in Japanese quail might be associated with dopaminergic system of the brain.